Structural and optical properties of the nc-Si:H thin films irradiated by high energetic ion beams - Goh, Boon Tong; Ngoi, Siew Kien; Yap, S.L.; Wong, C.S.; Dee, Chang Fu; Rahman, Saadah Abdul (2013)
Hydrogenated nanocrystalline silicon (nc-Si:H) thin films deposited by radio-frequency plasma enhanced chemical vapour deposition was irradiated by an energetic ion beam source from a 3.3 kJ Mather type dense plasma focus device. The effects of the energetic ion beam irradiations on the structural and optical properties of the nc-Si:H thin films have been studied. The results show that the formation of Si nano-crystallites embedded within the amorphous matrix was enhanced with an increase in the number of shots (up to 60) of irradiation. This significantly influences the optical properties of the films which include a widening of the optical band gap, a decrease in structure disorder and exhibiting a wide range of photoluminescence (PL) emission spectra at room temperature. Correlations of the PL peak energy and intensity with the optical energy gap, crystalline volume fraction, silicon suboxide content and its relationship to the oxide defects in the variation of number of shots are also discussed.